Classificação e quantificação das diferentes formas da dpoc pela tc de tórax - Remoli, Beatriz [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Chronic obstructive pulmonary disease or COPD is an obstruction of the air passage to the lungs that is usually associated with smoking or excessive exposure to pollution. COPD has two main components, chronic bronchitis and pulmonary emphysema. Both can affect the same patient and result in the worsening of their clinical condition. Based on the main changes found in Computed Tomography (CT) exams, this study aimed to understand the phenotype of the disease and how the tomographic exam can help in the screening, classification and quantification of lesions in patients affected by COPD. We also discuss the techniques used to perform the exam. Computed Tomography is one of the most efficient tests to diagnose and quantify COPD due to its excellent spatial resolution, differentiating normal lung parenchyma from areas of emphysema or gas retention. Thus, there has been an increasing indication for CT Chest in COPD, not only for its ability to characterize and classify the disease, but also has shown great potential to quantify the changes, establishing, together with the Pulmonary Function Test, the severity of the disease.

A doença pulmonar obstrutiva crônica ou DPOC trata-se de uma obstrução da passagem do ar até os pulmões que geralmente está associada a tabagismo ou devido à exposição excessiva a poluição. A DPOC possui dois componentes principais, a bronquite crônica e o enfisema pulmonar. Ambos podem acometer o mesmo paciente e resultar no agravamento de seu quadro clínico. A partir das principais alterações encontradas nos exames de Tomografia Computadorizada (TC), o presente trabalho teve por objetivo compreender o fenótipo da doença e como o exame tomográfico pode auxiliar no rastreio, classificação e quantificação das lesões nos pacientes acometidos pela DPOC. Discutimos também as técnicas utilizadas para a realização do exame. A Tomografia Computadorizada é um dos exames mais eficientes para diagnosticar e quantificar a DPOC devido à sua excelente resolução espacial, diferenciando o parênquima pulmonar normal das áreas de enfisema ou retenção gasosa. Assim, tem ocorrido uma crescente indicação da TC de Tórax na DPOC, não só pela sua capacidade de caracterizar e classificar a doença, mas também tem mostrado grande potencial para quantificar as alterações, estabelecendo, junto com a Prova de Função Pulmonar, a gravidade do quadro.
Classification and quantification of different forms of copd by thorax ct
Keywords: Chronic obstructive pulmonary disease (COPD); Computed tomography of the chest; Pulmonary emphysema; Chronic bronchitis; Asthma; Doença pulmonar obstrutiva crônica (DPOC); Tomografia computadorizada do tórax; Enfisema pulmonar; Bronquite crônica; Asma